Fluorescent Detection of Bromoperoxidase Activity in Microalgae and Planktonic Microbial Communities Using Aminophenyl Fluorescein - Archer, Stephen D.; Posman, Kevin M.; DeStefano, Janice; Harrison, Amelia O.; Ladina, Albertha; Cheff, Elizabeth A.; Witt, Daniel P. (Frontiers in Marine Science, 2019)
Among planktonic communities haloperoxidase enzymes may play a role in the control of intracellular and extracellular reactive oxygen species, in the generation of halogenated organic compounds and in chemical interactions between microbes. We introduce a sensitive fluorometric assay with a large dynamic range that is based on the dearylation of aminophenyl fluorescein (APF) to fluorescein by highly reactive oxygen species. Bromoperoxidase and chloroperoxidase enzymes catalyze the reaction between hydrogen peroxide and halides to generate highly reactive hypohalite intermediates able to dearylate APF. The fundamentals and standardization of the approach are illustrated using a partially purified, vanadium-dependent bromoperoxidase from the red seaweed Corallina officinalis. Laboratory cultures of two polar diatoms, Porosira glacialis and Fragilariopsis cylindrus, are used to illustrate the sensitivity and potential applications of the approach for in vitro, in vivo and in situ measurements of bromoperoxidase activity. These two diatoms differ in biovolume-specific bromoperoxidase activity by 2-orders of magnitude, from 5.4 to 0.044 fmol fluorescein μm-3 h-1, respectively. The approach is also used to investigate the partition of haloperoxidase activity between different size fractions of summer coastal planktonic communities, illustrating that generally more than 50 % of the haloperoxidase activity occurred in a > 10 μm size fraction that was dominated by diatoms. The assay has the potential to be of value in many aspects of haloperoxidase research, including developing an improved understanding of the roles of haloperoxidase enzymes in microbial planktonic communities.